Isolated cutaneous myeloid sarcoma preceding acute myeloid leukemia: a case report and literature review - Mavridou, Konstantina; Gavriil, Sofia; Papoudou-Bai, Alexandra; Gaitanis, George; Piperidou, Alexia; Bassukas, Ioannis D. (Dermatology Reports, 2024)
Isolated cutaneous myeloid sarcoma (icMS) and aleukemic leukemia cutis (ALC) are cutaneous extramedullary manifestations of leukemia in which leukemic cells infiltrate the skin before they can be identified either in the peripheral blood or in the bone marrow. We report the case of a 67-year-old patient who presented with a rapidly developing cutaneous tumor and scaly, erythematous- squamous plaques. Isolated cutaneous myeloid sarcoma was diagnosed, which rapidly progressed to terminal-stage acute myeloid leukemia (AML). To highlight the disease characteristics of the adult-onset icMS and ALC cases that preceded AML, we additionally compiled the pertinent literature of case reports of these rare conditions. We identified 15 previously published icMS/ALC cases with adequately detailed clinical data descriptions. We could confirm medical experience that icMS/ALC patients have a worse overall prognosis. Moreover, we could identify FAB-M5 AML subtype as a significant adverse prognosticator in these patients.